The Process and Function of Rebana Music Gendukan Jawan As A Communication of Kelompok Informasi Masyarakat (Kim) - Dalori, Dalori; Sumaryanto, Toto; Utomo, Udi (Catharsis, 2019)
The art of rebana traditional music Gendukan Jawan is one of religious-ethnic music styles used as communication media of Kelompok Informasi Masyarakat (KIM). The observed problem was how the process and function of rebana music Gendukan Jawan as a communication media of Kelompok Informasi Masyarakat (KIM) to the community of Kraton Kidul Pekalongan. The purpose of this research is to describe the process and function of rebana music of Gendukan Jawan as a communication media. The benefit of this research is to give contribution to all parties about rebana music Gendukan Jawan theoretically and practically. This study used qualitative method with interdisciplinary approach. The data collecting technique was observation, interview, and document study. The data validity used data triangulation technique. The data analysis used data reduction, data presentation, and conclusion drawing. The results show that the communication process of rebana music Gendukan Jawan of Kelompok Informasi Masyarakat (KIM) with Kraton Kidul community includes five elements as a respond from the five questions: Ã‚Â·1) Who : communicator 2) Say What : sent messages 3) In Which Channel : channel or media used to deliver the communication messages. 4) To Whom : receiver of the messages 5) With what Effect : the changes happened. The communication process involves primary communication process using verbal symbols namely messages that sent through song lyrics. Then, the secondary communication process using tools as the second media after using symbols as the first media. The function of rebana music Gendukan Jawan in Kelompok Informasi Masyarakat includes the function of telling, educating, changing the perception, and entertaining.